Effect of E-Filling System Implementation And Taxpayer Knowledge In Using E-Filling On Individual Taxpayer Compliance - Henny Zurika Lubis (AIBPM Publisher, 2019)
The purpose of this research is to study the application of the e-filling system of private taxpayers. To find out the understanding of taxpayers in the use of e-filling of personal taxpayers obligations, the discussion in this study is associative, The population in this study is all employees civil society in Medan City Housing and Structuring Agency that accommodates 152 people. The sample in this study were all civil servants outside the Financial and Compilation Program which examined 40 people. Data collection techniques used in this study were the study of documentation and questionnaires. Data analysis techniques used are multiple linear regression, hypothesis testing and coefficient of determination test. Based on the results of the evaluation between the application of the e-filing system to the demands of individual taxpayers obtained tcount (2.784)> ttable (1.686), with a significant level of 0.007 ttable (1.686), with a significant level of 0.001